Prevalence of Disordered Eating and Its Associated Factors From a Socioecological Approach Among a Sample of Spanish Adolescents: The EHDLA Study - José Francisco López-Gil; José Francisco López-Gil; José Francisco López-Gil; Estela Jiménez-López; Rubén Fernández-Rodríguez; Miram Garrido-Miguel; Miram Garrido-Miguel; Desirée Victoria-Montesinos; Héctor Gutiérrez-Espinoza; Pedro J. Tárraga-López; Arthur Eumann Mesas; Arthur Eumann Mesas (International Journal of Public Health, 2023)
Objectives: The aim of this study was twofold: a) to establish the prevalence of adolescents with disordered eating and b) to determine the factors associated with this prevalence in a sample of Spanish adolescents from the Valle de Ricote (Region of Murcia, Spain).Methods: This cross-sectional study analyzed data from 730 adolescents (56.2% girls) from the EHDLA study. To determine the prevalence of disordered eating, the Sick, Control, One stone, Fat, Food (SCOFF) questionnaire was used. A socioecological approach was used to identify individual-, interpersonal-, or organizational-level factors associated with disordered eating.Results: The prevalence of disordered eating was 30.1%. This condition was associated with female sex (odds ratio [OR] = 2.60; 95% confidence interval [CI], 1.81–3.73), immigrant status (OR = 2.22; 95% CI, 1.51–3.25), or excess weight (OR = 2.74; 95% CI, 1.93–3.89). Furthermore, for each additional hour slept, lower odds of having disordered eating were found (OR = 0.81; 95% CI, 0.67–0.98).Discussion: Almost one-third of the sample of Spanish adolescents analyzed reported disordered eating. Female sex, immigrant status and excess weight are individual aspects that seem to be related to disordered eating among Spanish adolescents.